A Compact Model of Ovonic Threshold Switch Combining Thermal Dissipation Effect - Zhang, Shiqing; Xu, Hui; Li, Zhiwei; Liu, Sen; Song, Bing; Li, Qingjiang (Frontiers in Neuroscience, 2021)
Ovonic threshold switch (OTS) has received great attention in neuromorphic computing due to its support for high-density synapse array as a selector and leaky-integration-firing functions Hodgkin-Huxley neurons. However, there is no simple and complete model for device simulation and integrated circuit design, which hindered application until now. In this work, we developed a compact physical model of ovonic threshold switch based on Poole-Frenkel effect accompanied by thermal dissipation effect for the first time. The thermal dissipation effect describes energy flow between the device and the environment so that the model is more practical. Compared with previous experiments, the numerical results fairly fitted the electrical characteristics, demonstrating the model validity. In addition, relation of device performance with material and structure was deduced, which can facilitate optimizing the OTS device. The model will be useful for device design and implemented with high speed for simplicity.